2019
DOI: 10.3390/md17120708
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin-Soluble Collagen from the Skin of Lophius litulo: A Preliminary Study Evaluating Physicochemical, Antioxidant, and Wound Healing Properties

Abstract: The structure of pepsin-solubilized collagen (PSC) obtained from the skin of Lophius litulon was analyzed using the sodium dodecylsulphate polyacrylamide gel electrophoresis (SDS-PAGE), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). SDS-PAGE results showed that PSC from Lophius litulon skin was collagen type I and had collagen-specific α1, α2, β, and γ chains. FTIR results indicated that the infrared spectrum of PSC ranged from 400 to 4000 cm−1, with five main amide ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…Other biological activities such as anti-glycation [ 193 ], anti-inflammatory [ 194 197 ], anti-microbial [ 198 , 199 ], anti-coagulant [ 200 204 ], anti-ageing [ 205 209 ] and anti-obesity [ 208 , 209 ] have also been recognized in seaweed polysaccharides.…”
Section: Advanced Extraction Methodologies For Algal Polysaccharidesmentioning
confidence: 99%
“…Other biological activities such as anti-glycation [ 193 ], anti-inflammatory [ 194 197 ], anti-microbial [ 198 , 199 ], anti-coagulant [ 200 204 ], anti-ageing [ 205 209 ] and anti-obesity [ 208 , 209 ] have also been recognized in seaweed polysaccharides.…”
Section: Advanced Extraction Methodologies For Algal Polysaccharidesmentioning
confidence: 99%
“…PSC obtained from the skin of Lophius litulon was also tested. It has been shown to possess both antioxidant properties in vitro based on its ability to scavenge different free radicals, such as DPPH, ABTS·, HO·, and O 2 - and increase the content of superoxide dismutase (SOD) and catalase (CAT), and wound healing activity in mice model [ 87 ]. Collagen from red tilapia Oreochromis sp.…”
Section: Fish Byproducts As Source Of High Added-value Compoundsmentioning
confidence: 99%
“… Skin regeneration, antibacterial 30 mg/kg BW [ 84 ] Collagen Skin Oreochromis sp. Wound healing Not specified [ 85 ] Collagen Scale Ctenopharyngodon idellus Wound healing Not specified [ 86 ] Collagen Skin Lophius litulon Antioxidant, wound healing 1–8 mg/mL4 g/day [ 87 ] Collagen Skin Oreochromis sp. Antioxidant 2–7 mg/mL [ 88 ] Collagen/chitosan Skin Not specified Antioxidant 12–100 μg/mL [ 89 ] Collagen/gelatin Skin Priacanthus hamrur Antioxidant, antibacterial DPPH and ABTS 1 mg/mL Antibacterial 200 μg [ …”
Section: Fish Byproducts As Source Of High Added-value Compoundsmentioning
confidence: 99%
“…The meat is usually made for human consumption, and the by-product skin is often treated as waste or used for making fish food ( 29 ). In our previous study, on which this study is based, we evaluated the physicochemical properties of extracts collected from the skin of monkfish ( Lophius litulon ) with pepsin (pepsin-solubilized collagen, PSC) and showed that PSC has good antioxidant and wound healing activity ( 30 ). In this study, PSC was hydrolyzed to obtain collagen peptides (pepsin-solubilized collagen peptide, PSCP) with higher antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%